The relationship of disordered eating habits and attitudes to clinical outcomes in young adult females with type 1 diabetes. - Peveler, R; Bryden, K; Neil, H; Fairburn, C; Mayou, R; Dunger, D; Turner, H (2005)
OBJECTIVE: To describe the clinical outcomes of adolescent and young adult female subjects with type 1 diabetes in relation to the disturbance of eating habits and attitudes over 8-12 years. RESEARCH DESIGN AND METHODS: Patients were recruited from the registers of pediatric and young adult diabetes clinics (including nonattenders) and interviewed in the community. A total of 87 patients were assessed at baseline (aged 11-25 years), and 63 (72%) were reinterviewed after 8-12 years (aged 20-38 years). Eating habits and attitudes were assessed by a semistructured research diagnostic interview (Eating Disorder Examination). RESULTS: Clinical eating disorders ascertained from the interview and/or case note review at baseline or follow-up were found in 13 subjects (14.9% [95% CI 8.2-24.2]), and an additional 7 subjects had evidence of binging or purging, bringing the total affected to 26%. Insulin misuse for weight control was reported by 31 (35.6% [25.7-46.6]) subjects. Overall outcome was poor; serious microvascular complications were common and mortality was high. There were significant relationships between disordered eating habits, insulin misuse, and microvascular complications. CONCLUSIONS: Although the cross-sectional prevalence of clinical eating disorders in young women with diabetes is modest, the cumulative incidence of eating problems continues to increase after young adulthood, and this is strongly associated with poor physical health outcomes. The combination of an eating disorder and diabetes puts patients at high risk of mortality and morbidity. Better methods of detection and management are needed.